Daya Hambat Krim Minyak Atsiri Herba Boborangan (Hyptis brevipes) sebagai antibakteri terhadap Staphylococcus aureus - Arviani - Arviani; Dwi Larasati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Boborongan (Hyptis brevipes) is empirically used in ethnomedicine containing of essential oil which it is applied to inhibit the growth of the Staphyllococcus aureus. Cream preparation along with oil in water emulsion is often applied due to easiness and compliance particulary for  cosmetic and aesthetic use. This study aimed to determine the minimum inhibitory concentration of cream based essential oil of Hyptis brevipes against Staphylococcus aureus. Essential oil from Hyptis brevipes was isolated using the water vapor distillation method. Cream based essential oil of Hyptis brevipes of 0.1%, 0.2%, and 0.4%, respectively. Antibacterial activity study was carried out using a well diffusion method. Antibacterial inhibition was obtained by measuring the clear zone on the medium. The results of the antibacterial inhibition test showed that the cream based Hyptis brevipes essential oil along with concentration of 0.1%, 0.2%, and 0.4% showed antibacterial activity with the diameter of inhibition zone are 5.3 mm; 5.1 mm; and 6 mm, respectively. Therefore, it prooved that the essential oil of Hyptis brevipes was a promising candidate for antibacterial substance